Appraisal of Internet Surfing and Television Viewing in Nigeria - Omolara Oluwabusayo Akin-Odukoya; Olubunmi Felicia Adedoyin; Funmi Falobi; Omotola Ogunbola (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
The evolution of media consumption in Nigeria reflects the country’s dynamic cultural, technological, and economic landscape. Internet surfing and television viewing have become significant aspects of everyday life, influencing education, entertainment, communication, and socio-economic development. This appraisal explores trends, impacts, and challenges while offering recommendations for optimizing media consumption in Nigeria. An appraisal of internet surfing and television viewing in Nigeria reveals both opportunities and challenges. While these platforms have transformed education, communication, and entertainment, they also pose risks that require careful management. By addressing the digital divide, fostering local content, and promoting media literacy, Nigeria can harness the benefits of modern media while mitigating its drawbacks. The paper argues that the Internet has become a basic tool for trading, entertainment, and communication, as well as education, in the contemporary world. Nevertheless, despite its positive uses, the presence of additive behaviours among some Internet users has drawn the attention of the public and helping professionals. The paper concludes that the interplay between internet surfing and television viewing in Nigeria is shaping the cultural and economic fabric of the nation. While these media provide opportunities for growth, education, and connectivity, their unregulated use presents risks, especially to younger audiences. A collective effort from stakeholders, including the government, media industry, educators, and families can help harness the potential of these platforms while mitigating their challenges.